1982
DOI: 10.1002/kin.550140903
|View full text |Cite
|
Sign up to set email alerts
|

Pyridiniumchlorochromate oxidations: Studies on the kinetics and substituent effect in the oxidation of aniline in nonaqueous systems

Abstract: Pyridiniumchlorochromate (PCC) oxidizes aniline and substituted anilines except nitro anilines smoothly in chlorobenzene-nitrobenzene mixtures in the presence of dichloroacetic acid. The reaction has unit dependence on each of the aniline, PCC, and dichloroacetic acid concentrations. Electron-releasing substituents accelerate the reaction, whereas electronwithdrawing groups retard the reaction, and the rate data obey Hammett's relationship. The reaction constant p is -3.75. Azobenzene and p-benzoquinone have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

1983
1983
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…The values of the reaction constant, ρ, were found to be negative, which confirms the formation of a positively charged transition state. The reaction constants obtained in the present study are comparable to those of previously reported oxidation of anilines by various oxidants (percarbonate, ρ = −2.7 [28]; perborate, ρ = −3.0 [29]; pyridinium chlorochromate, [30], and imidazolium fluorochromate, ρ = −2.22 [31]). …”
Section: Structure-reactivity Correlationsupporting
confidence: 90%
“…The values of the reaction constant, ρ, were found to be negative, which confirms the formation of a positively charged transition state. The reaction constants obtained in the present study are comparable to those of previously reported oxidation of anilines by various oxidants (percarbonate, ρ = −2.7 [28]; perborate, ρ = −3.0 [29]; pyridinium chlorochromate, [30], and imidazolium fluorochromate, ρ = −2.22 [31]). …”
Section: Structure-reactivity Correlationsupporting
confidence: 90%
“…The negative ρ value is indicative of the presence of a positive nitrogen center, which would mean depletion of lone‐pair electron density, and this can be facilitated only when the oxidant forms a complex with the substrate in which the nitrogen lone‐pair can be used up in coordinating with an electron‐deficient center, preferably a metal ion. Similar mechanism has been postulated for the oxidation of anilines by pyridinium chlorochromate in chlorobenzene–nitrobenzene mixture 16 and by nicotinium dichromate in benzene‐ tert ‐butanol mixtures 22. Further, such a complex formation is supported by the negative entropy of activation observed.…”
Section: Resultssupporting
confidence: 56%
“…The negative reaction constant indicates the formation of a positively charged activated complex with extensive bond formation between the reactants 6. The reaction constant is comparable to that of the percarbonate oxidation of molecular aniline in glacial acetic acid (ρ = −2.7 ± 0.1 14), perborate oxidation of molecular aniline in glacial acetic acid (ρ = −3.0 15), pyridinium chlorochromate oxidation of anilines in chlorobenzene‐nitrobenzene mixtures (ρ = −3.75 16), and imidazolium fluorochromate oxidation of anilines in DMF (ρ = −2.22 17). The specific rate constants for the meta‐ and para‐substituted anilines correlate satisfactorily with σ + (0.841 < r < 0.936, 0.31 < SD < 0.62, −1.33 ± 0.21 < slope < −2.03 ± 0.41) and σ p and σ m (0.900 < r < 0.966, 0.26 < SD < 0.47, −1.51 ± 0.19 < slope < −2.28 ± 0.32) also.…”
Section: Resultsmentioning
confidence: 67%
“…The correlations of log k obs versus pK a [22] and log k obs versus pK a (= pK a -substituted aniline -pK a aniline) [23] are nonlinear. This observation along with the results of structure-reactivity correlation indicates that molecular anilines are the reactive species [24].…”
Section: Mechanismmentioning
confidence: 98%